Evaluasi Penggunaan Digital Library SMA Negeri di Kabupaten Buleleng - R.K.R.M. Sudibyo; I.G.K.A. Sunu; I.N. Natajaya (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aims to 1) determine the effectiveness of the digital library from the context component; 2) determine the effectiveness of the digital library of the input components; 3) determine the effectiveness of the digital library of process components; 4) determine the effectiveness of the digital library of product components; 5) knowing the effectiveness of digital libraries together in context, input, process, product; and 6) knowing the obstacles in using digital libraries at SMA Negeri Buleleng Regency. The research was conducted at SMAN 1 Singaraja, SMAN 1 Banjar, SMAN 1 Seririt, and SMAN Bali Mandara. This study uses a quantitative approach, this study uses an evaluation research design. The population in this study were all teachers from the 4 schools. The research sample was determined by using purposive sampling technique. Data were collected using questionnaires, documentation and interviews. Data analysis was carried out by converting the raw score into a Z score (z-score) followed by a T score and then converted into the Glickman quadrant. The results showed the effectiveness of using a digital library in terms of the context obtained effective results (+), the effectiveness of the use of digital libraries in terms of input obtained effective results (+), the effectiveness of using digital libraries in terms of process obtained less effective results (-), the effectiveness of using digital libraries in terms of the product obtained effective results (+). Overall, the evaluation of context, input, process, and product variables on the use of the digital library of SMA Negeri in Buleleng Regency is considered effective (+ + - +)